Determinants of Food Waste Behaviors Among Muslim Consumers in Surabaya: The Role of Religiosity and Food Consumption Culture - Adam Zulvan; Trapsila, Aji Purba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Food waste behavior is closely related to individual consumerist attitudes, which in an Islamic context can be categorized as tabzir. This study aims to identify the factors influencing food waste behavior among Muslim consumers in Surabaya. The study uses the Theory of Planned Behavior (TPB) model and two contextual factors, namely religiosity and food consumption culture, to explain food waste behavior. Data were analyzed using PLS-SEM (Partial Least Square - Structural Equation Modelling) with the assistance of SmartPLS 4 software. The results indicate that all TPB variables significantly influence the intention to reduce food waste, with attitude being the most significant predictor of the intention to reduce food waste. Furthermore, the variables of intention, perceived behavioral control (PBC), religiosity, and food consumption culture also have a significant influence on food waste behavior. High levels of religiosity can inhibit individuals from engaging in food waste, while an unwise food consumption culture will encourage food waste. This study concludes that to prevent food waste behavior, it is necessary to integrate Islamic consumption principles with sustainable consumption culture among Muslims.